The Improvement of Mathematics Learning of Trigonometry on Students in Class X-Tei of SMK Negeri 1 Situbondo by Using STAD Method - Sidawi Sidawi (Pancaran Pendidikan, 2021)
This research aimed to analyze Mathematics learning on Vocational High School students by using STAD learning model on Trigonometry material. By using acquisition processing skills, students will be able to discover and develop their own facts and concepts as well as growing and developing attitudes and values. This research used a classroom action research (CAR) design. Data collection tools and methods used in this research were tests, observations, and questionnaires. The results showed that the average score of students in cycle 1 was 69.84 with the lowest score as much as 61 and the highest score was 79. The limit for learning completeness was 65, the number of students who scored 65 as many as 27 students, which means 81.82% out of 32 students had a value in the top level of mastery of a given concept, or more than 80%. The average score of students in cycle 2 was 76.15 with the lowest score as much as 68 and the highest was 87. The limit for learning completeness was 65, the number of students who scored 65 as many as 32 students, which means that 100% of the students had grades at the top level of mastery of the given concept, or more than 80%. From cycle II, it can be said that the learning process has succeeded in achieving what has been targeted. Thus, it can be said that the learning process has met what was expected, namely an increase in the quality of learning as indicated by an increase in the quality of students’ achievement as a whole